Synergistic therapeutic effect of Guggul gum resin on antidiabetic activity of saxagliptin - Shalini Jain; Mukesh Kumar Sharma; Asad Syed; Ali H. Bahkali; Surendra Nimesh; Nidhi Gupta; Sreemoyee Chatterjee (Journal of Agriculture and Food Research)
Type 2 Diabetes Mellitus is an endocrine metabolic disorder leading to impaired glucose utilization. This disease is managed by both commercial drugs and herbal products eliciting various interactions. The evaluation of one such interaction between saxagliptin (SAXA, substrate of CYP3A4), and Guggul extract (GE) from Commiphora wightii is done in this present study. The concomitant administration of the SAXA with GE had restored the levels of otherwise increased blood glucose and biochemical parameters and otherwise decreased total glycogen and oxidative stress markers more effectively as compared to the solely consumed SAXA or GE. These results were corroborated by histopathological evaluation where the combination treatment showed better mitigation of hepatic, renal and pancreatic tissue damage that occurred due to induced diabetes. Furthermore, CYP3A11 mRNA (murine homolog to human CYP3A4) expression levels were observed to be reduced to non-diabetic levels in combination therapy which was otherwise unachievable. The molecular docking studies predicted improved interaction between CYP3A4 and bioactive content of GE, i.e., guggulsterone E-Z, possessing binding energy of −9.96 kcal/mol along with SAXA, confirming the co-existence of both the ligands at different binding sites of the metabolizing enzyme. The synergistic interactions of GE and SAXA helped in better restoration of tissue damage and increased CYP3A11 mRNA expression levels caused by induced diabetes.